Lack of Interference of Guanosine with Ribavirin Aerosol Treatment of Influenza A Infection in Mice - Knight, Vernon (1981)
Guanosine or guanosine 5′-monophosphate did not reduce the protective effect of ribavirin aerosol in influenza virus A/Aichi/68 H3N2 infection of mice. Both compounds partially interfered with the action of a wide range of ribavirin concentrations against influenza virus A/WSN replication in cell culture.